Coupled mesoscale–microscale modeling of air quality in a polluted city using WRF-LES-Chem - Y. Wang; Y.-F. Ma; D. Muñoz-Esparza; J. Dai; C. W. Y. Li; P. Lichtig; R. C.-W. Tsang; C.-H. Liu; T. Wang; G. P. Brasseur; G. P. Brasseur; G. P. Brasseur (Atmospheric Chemistry and Physics, 2023)
To perform realistic high-resolution air quality modeling in a polluted urban area, the Weather Research and Forecasting (WRF) model is used with an embedded large-eddy simulation (LES) module and online chemistry. As an illustration, a numerical experiment is conducted in the megacity of Hong Kong, which is characterized by multi-type inhomogeneous pollution sources and complex topography. The results from the multi-resolution simulations at mesoscale and LES scales are evaluated by comparing them with ozone sounding profiles and surface observations. The comparisons show that both mesoscale and LES simulations reproduce the mean concentrations of the chemical species and their diurnal variations at the background stations well. However, the mesoscale simulations largely underestimate the NOx concentrations and overestimate O3 at the roadside stations due to the coarse representation of the traffic emissions. The LES simulations improve the agreement with the measurements near the road traffic, and the LES with the highest spatial resolution (33.3 m) provides the best results. The large-eddy simulations show more detailed structures in the spatial distributions of chemical species than the mesoscale simulations, highlighting the capability of LES to resolve high-resolution photochemical transformations in urban areas. Compared to the mesoscale model results, the LES simulations show similar evolutions in the profiles of the chemical species as a function of the boundary layer development over a diurnal cycle.